WAQF FUND MANAGEMENT MODEL IN THAILAND: CASE STUDY OF AL-HIDAYAH WAKAF FOUNDATION FOR EDUCATION AND SOCIAL DEVELOPMENT - Huriyah, Siti; Alhifni, Anas; Kurnia, Tuti; Munawar, Wildan (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This research aims to find out the management of waqf funds at the Al Hidayah Waqf Foundation for Education and Social Development, and the model of waqf funds management at the Al Hidayah Waqf Foundation for Education and Social Development, particularly in the management of Education in South Thailand. Research methods using qualitative descriptives, data analysis techniques using Fishbone diagrams, and data collection through interviews. The research results show that the Al Hidayah Wakaf Foundation for Education and Social Development has a waqf property of 15 million Baths or around 7 billion, to find out the waqf fund management model at the Al-Hidayah Waqf Foundation for Education and Social Development by providing education scholarships to foreign countries such as Indonesia, Malaysia, and Medina or Muslim-based countries.